PEMBELAJARAN MATEMATIKA BERBASIS TIK BERUPA VIDEO PEMBELAJARAN MENGGUNAKAN STORYBOARD - Irma Santika; Sumianah; Agung Wintoro; Sri Mulyaningsih; Muthiah Rahman; Abdul karim (CV. ADIBA AISHA AMIRA, 2024)
The objectives of this research are (1) to explain the meaning of Information and Communication Technology (ICT); (2) explain the importance of using ICT in Mathematics Learning; (3) describe how much ICT is used in Mathematics Learning in Indonesia; (4) describes the positive and negative impacts of applying ICT in Mathematics learning. The method used is a literature review and descriptive interviews with educators and students in the field of mathematics education. Information and Communication Technology is electronic equipment consisting of hardware and software as well as all activities related to processing, manipulation, management and transfer of information between media. Its function is to produce quality and communicative information. In Indonesia, the use of Information and Communication Technology is still at the level of integration, which is shown by the use of technology in learning. The use of information technology, apart from being an effort to overcome technical problems of learning as a learning medium, is also an effort to answer substantial problems of learning as a teaching resource and encourage the acceleration of computer literacy in Indonesian society. This article aims to discuss the effectiveness of online-based mathematics learning (E-learning) on student learning achievement. So the development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that plays a role in the world of education is online learning (E-learning). Online learning (E-learning) functions as a link between educators and students using electronics and internet networks that can be accessed anytime and anywhere. The online media used are various (WhatsApp, Google Classroom, YouTube). The aim of this research is to analyze the effectiveness of online-based mathematics learning (E-learning). The method used in collecting data is to provide an evaluation.